Elaboración de un modelo de gestión administrativa para el supermercado “Sumesa” en la ciudad de Shushufindi, cantón Shushufindi, provincia de Sucumbíos, para el año 2016 - Macías Carpio, Carla Lorena (2017)
The modern administration states that the success of any company or organization, basically depend on the dynamics of its administrators and the proper use and use of different management systems, taking this premise as a starting point for the preparation of this thesis work , whose general objective was "Design an Administrative Management Model for the Supermarket" SUMESA "of the City of Shushufindi" in order to increase the efficiency in the management of the services offered, improving the internal and external customer satisfaction. The methodology used during the development of the present investigation was based on the use of the methods: deductive, inductive, analytical and statistical, while for the collection of the information the observation was applied, the Manager interviewed and the 15 workers polled. In the internal diagnosis made it is evident that in the Supermarket "Sumesa" their administrative processes lack the administrative technical guarantee that guarantee their continuity and business development since they do not execute planning activities that guarantee the effective and efficient fulfillment of their main goals and objectives which does not allow it to be dynamic and fully guarantee what is proposed. There was a limited application of the administrative process, as they have mission and vision but do not have a structural organization chart, manual functions or procedures, as stated by the manager and ratified by 100% of employees and workers; The objectives and strategies are based on experiences rather than prior to a technical analysis that contributes to improving decision making. A job profile has not been defined for the recruitment of personnel. 93% of the staff is not offered motivation to make their work more efficient, and 100% of the staff report that they are not given the opportunity to advance in the company, finally 80% of the workers do not receive training. Faced with these needs, a model was considered that contemplates the four phases of the administrative process: planning, organization, direction and control. In each of the phases, tools are proposed that will contribute to improving the efficiency in the use of the resources available to the supermarket, which in turn will improve its profitability. Finally, it is recommended to implement the proposed administrative management model, since it will guarantee and ensure that all the work activities deployed comply with the plans and objectives of the Supermarket.